1999
DOI: 10.1038/sj.bmt.1701672
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a graft-versus-leukemia reaction by cyclosporin A withdrawal as immunotherapy for leukemia relapsing after allogeneic bone marrow transplantation

Abstract: Summary:We studied the immunomodulating effect of withdrawal of immunosuppression with cyclosporin A (CsA) in 42 patients with leukemic relapse of chronic myelogenous leukemia (CML) (n ‫؍‬ 24), acute myeloid leukemia (AML) (n ‫؍‬ 13) and acute lymphoblastic leukemia (ALL) (n ‫؍‬ 5) after allogeneic unmanipulated bone marrow (BMT) or peripheral blood stem cell transplantation (PBSCT). Response to CsA withdrawal was monitored molecularly by the polymerase chain reaction for elimination of CML cells containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…The results suggested that cyclosporin could safely be discontinued early in patients who never had evidence of acute GVHD, but those patients with preceding acute GVHD may have benefited from a longer course of the drug in order to delay the onset and possibly the incidence of chronic GVHD. More recently Elmaagacli et al 21 have similarly demonstrated that cyclosporin A withdrawal in relapsing CGL and AML patients could initiate a graft-versus-leukaemia (GVL) reaction, often however, also giving rise to severe GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that cyclosporin could safely be discontinued early in patients who never had evidence of acute GVHD, but those patients with preceding acute GVHD may have benefited from a longer course of the drug in order to delay the onset and possibly the incidence of chronic GVHD. More recently Elmaagacli et al 21 have similarly demonstrated that cyclosporin A withdrawal in relapsing CGL and AML patients could initiate a graft-versus-leukaemia (GVL) reaction, often however, also giving rise to severe GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In all, insufficient post transplant immunosuppression is one of the most important determinants of relapse risk through its impact on the potency of an immunologically mediated graft vs. malignancy effect. This is particularly relevant in patients undergoing allogeneic HSCT using a reduced-intensity conditioning regimen, where a graft vs. malignancy effect represents the dominant anti-tumour mechanism [4,[17][18][19][20][21][22]. Therefore, a model that predicts ciclosporin pharmacokinetics and dose requirements to achieve the desired therapeutic target in an individual HSCT patient would be highly useful.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of defining the relapse probability has gained increasing attention since the reduction or withdrawal of immunosuppression early after transplantation [2] and the use of donor leukocyte infusions (DLI) [3] are options to diminish the risk of relapse and improve outcome after HSCT. However, there are no established markers available that predict the risk of relapse independent from cytogenetic/mutational status [4,5] or disease stage [6,7].…”
Section: Introductionmentioning
confidence: 99%